Biodiversity of oribatid mites (Acari: Oribatida) along an altitudinal gradient in the Central Alps - Fischer, Barbara M.; Schatz, Heinrich (Zootaxa, 2013)
Oribatid mite communities were studied in the Central Alps(Obergurgl, Tyrol, Austria). Samples were taken on four sites along an altitudinal gradient from 2050 m a.s.l to 2900 m a.s.l., in different vegetation units (pine forest, Nardetum, Caricetum, Androsacetum). A total of 86 species were found, most of them occurred only at one altitude, four species were found in all four study sites. Three taxa could not be ascribed to a certain species (Carabodes sp. Mycobates sp., Tectocepheus sp.). Species richness and density of oribatid mites decrease with increasing altitude. The results are compared with previous studies in the same region and show remarkable shifts in species composition.